Exacerbation of Recalcitrant Cutaneous Sarcoidosis with Adalimumab - a Paradoxical Effect? A Case Report - Santos, G (2014)
Submitted by Ana Quininha (ana.quininha@chlc.min-saude.pt) on 2014-05-23T16:05:29Z No. of bitstreams: 1 An Bras Dermat 2013 s26.pdf: 253959 bytes, checksum: 761d50d916466fa3b2c639a4d2f463cd (MD5)